The constitutional protection of fundamental liberties in Malaysia with special reference to freedom of speech and expression / Sharon Kaur Chahil Chet Sin - Sharon Kaur, Chahil Chet Sin (1996)
Human rights with particular reference to civil and political rights. The ethics refers to the legal documents which contains some of the international human rights standard to be discussed here.